2019
DOI: 10.1149/2.0021901jss
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Electrochromic Performance by Embedding ITO Nanocrystals in Amorphous WO3 Film

Abstract: The electrochromic films featuring the well dispersed ITO nanocrystal (about 10 nm) in amorphous WO 3 (ITO@WO 3 ) have been successfully fabricated with a solution process. The structure and electrochromic properties of the as-prepared films were studied by high resolution transmission electron microscope, scanning electron microscope, X-ray photoelectron spectroscopy, X-ray diffraction, and electrochemical methods. The measured coloration/bleach time decreases from 10.5/27.8 s to 5.7/0.9 s with the increasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 25 publications
2
9
0
1
Order By: Relevance
“…The calculated diffusion coefficients of Li + insertion are 2.78 × 10 −11 and 1.80 × 10 −11 cm 2 s −1 with and without MXene addition, respectively. Also, diffusion coefficients of Li + extraction are 1.04 × 10 −10 and 5.52 × 10 −11 cm 2 s −1 with and without MXene addition, which show the quantitative agreement with the previous studies [ 63 , 64 ]. The lithium ion insertion/extraction speed into the electrochromic film is evidently enhanced by the addition of MXene.…”
Section: Resultssupporting
confidence: 91%
“…The calculated diffusion coefficients of Li + insertion are 2.78 × 10 −11 and 1.80 × 10 −11 cm 2 s −1 with and without MXene addition, respectively. Also, diffusion coefficients of Li + extraction are 1.04 × 10 −10 and 5.52 × 10 −11 cm 2 s −1 with and without MXene addition, which show the quantitative agreement with the previous studies [ 63 , 64 ]. The lithium ion insertion/extraction speed into the electrochromic film is evidently enhanced by the addition of MXene.…”
Section: Resultssupporting
confidence: 91%
“…4(b), the optical modulation rate Δ T is up to 87.89% at wavelength 633 nm, which is higher than many reported electrochromic devices. 10,29–31 As illustrated in Table 1, the optical modulation has reached 90.28% around wavelength 749 nm. Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Here we report results from a study of In-containing WO3 thin films prepared by codeposition and demonstrate that the In content tends to deteriorate the electrochromism of WO3, thus giving clear evidence that SEI layers are the prevalent source of the boosted cycling durability of potentiostatically pretreated EC WO3 films. We are not aware of earlier work on EC W-In oxide films with metal ions being intermixed on an atomic or near-atomic scale, as in the present investigation; however, studies have been reported on nanocomposites of ITO embedded in WO3 [11][12][13][14][15][16] wherein ITO contributes to optical modulation rate (due to lowered electrical resistance) and modulation range (due to plasmonic effects [17][18][19][20]).…”
Section: Introductionmentioning
confidence: 77%